Analisis Kinerja Badan Permusyawaratan Desa (BPD) di Desa Japah Kecamatan Japah Kabupaten Blora - Puryanti, Marlina; Nurcahyanto, Herbasuki; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research aims to describe and analysis the performance of Badan Permusyawaratan Desa ( BPD ) at Japah village, Japah sub district, Blora district. Based on the results of the study indicate that performance of Badan Permusyawaratan Desa ( BPD ) has not quite succeeded in Japah vilage, while there are some criteria which is considered very successful, but more will be considered less successful writers. The criteria has not been successful is an effectiveness, input, productivity, and accountability.The conclusions of this study is the overall performance of Badan Permusyawaratan Desa ( BPD ) Japah has not succeeded. Contrainst are owned by limited budgets, limited support of infrastructure and the human resources inadequate. Based on these conclusions, the researchers recommend to Badan Permusyawaratan Desa ( BPD ) Japah to improve the criteria assessed to be less successful, so the performance of Badan Permusyawaratan Desa ( BPD ) Japah can be optimally achieved